2022
DOI: 10.15548/nsc.v8i1.3726
|View full text |Cite
|
Sign up to set email alerts
|

Capturing Student’s Profile of Nature of Science in Sekolah Indonesia Kuala Lumpur

Abstract: The purpose of this research is to analyze the profile of students’ Nature of Science (NOS) of 7th, 8th and 9th grade Junior High School in Sekolah Indonesia Kuala Lumpur. Descriptive method is used to describe the current condition of students’ Nature of Science (NOS) after science lesson on interaction of organisms and its environemnet topic conducted in the class. The data in this research is gained through constructed response item test that is given without any academics treatment before. The result shows… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The results indicated that promoting creativity among students has the potential to improve their capacity to participate in and excel at creative endeavors, leading to significant effects on their academic achievements. In another study [67], an examination was undertaken to investigate the correlation between individuals' perceived creativity and the Big Five personality qualities. The study's findings indicated that creativity has a crucial role in problem-solving and cognitive aptitude as adults' vocational and overall life achievements.…”
Section: Creativity and Cognition Interactionmentioning
confidence: 99%
“…The results indicated that promoting creativity among students has the potential to improve their capacity to participate in and excel at creative endeavors, leading to significant effects on their academic achievements. In another study [67], an examination was undertaken to investigate the correlation between individuals' perceived creativity and the Big Five personality qualities. The study's findings indicated that creativity has a crucial role in problem-solving and cognitive aptitude as adults' vocational and overall life achievements.…”
Section: Creativity and Cognition Interactionmentioning
confidence: 99%